위암에서의 p14ARF, p16INK4a, p53, pRb 단백 발현 - 채병주(Byung Joo Chae); 송교영(Gyo Young Song); 김진조(Jin Jo Kim); 진형민(Hyung Min Chin); 김욱(Wook Kim); 박조현(Cho Hyun Park); 전해명(Hae Myung Jeon); 박승만(Seung Man Park); 임근우(Keun Woo Lim); 김응국(Eung Kook Kim); 김승남(Seung Nam Kim) (Annals of surgical treatment and research, 2004)
Purpose: In this study, the level of expression of p14ARF, p16INK4a, p53 and pRb was immunohistochemically examined according to the stage of gastric cancer, lymph node metastasis, cell differentiation and Lauren's classification. The effect on survival rate and the associations between the components were examined as well. Methods: One hundred and fourteen patients who underwent surgery for gastric cancer were studied retrospectively using their paraffin embedded tissue and medical records. Using antibodies of p14ARF, p16INK4a, p53 and pRb, immunohistochemical stain was applied and their level of expression examined. Results: The level of p53 expression was high when the stage of gastric cancer was more progressed, the invasiveness higher, lymph node metastasis present and cell differentiation poorer. In contrast, the level of p14ARF expression tended to be lower as the stage was more progressed, but this was not statistically significant. Expression of p16 and pRb did not show any association with stage or other pathologic findings. Expression of p53 and p14ARF also had a significant association with survival rate. Survival rate was lower in patients who expressed p53 than in those who did not, but it was higher in who expressed p14ARF than in those who did not. When these two were combined, patients with p14ARF( )/p53( ) had the highest survival rate, whereas those with p14ARF( )/ p53( )had the lowest. This demonstrated that the expressions of p14ART and p53 have value as prognostic indicators. Conclusion: From these results, p53 seems closely related to stage and other pathologic findings. Furthermore, p14ARF and p53 showed a statistically significant relationship with survival rate, making them valuable as prognostic indicators after surgery. In combination, it would be possible to predict a more accurate prognosis. KCI Citation Count: 0